Mannose binding lectin‐associated serine protease 2 (MASP2) gene polymorphism and susceptibility to human T‐lymphotropic virus type 1 (HTLV‐1) infection in blood donors from Mashhad, Iran. (28th August 2022) - Aghamohammadi, Akram; Rafatpanah, Houshang; Maghsoodlu, Mahtab; Tohidi, Nastaran; Mollahosseini, Farzad; Shahabi, Majid
Abstract: Mannose binding lectin‐associated serine protease 2 (MASP2) is the effector part of mannose binding lectin (MBL) that activates the complement system in an antibody‐independent manner. We aimed to investigate the role of genetic polymorphisms in the MASP2 gene and susceptibility to HTLV‐1 infection. A total of 172 HTLV‐1 infected individuals and 170 healthy blood donors were analyzed in this case–control study. Nine single nucleotide polymorphisms (SNPs) encompassing different regions of the MASP2 gene were genotyped with a polymerase chain reaction‐sequence‐specific primer (PCR‐SSP) assay. The relation between the SNPs genotype and the susceptibility to HTLV‐1 infection was investigated with a χ 2 test considering P  < 0.05 as statistically significant. Two of nine tested SNPs were associated with the risk of HTLV‐1 infection. The genotype TT at rs17409276 decreased the risk of HTLV‐1 ( P  = 0.005, OR = 0.301, 95% CI = 0.124–0.728). The genotypes CC and CT at rs2273346 were also associated with a higher risk of HTLV‐1 acquisition ( P  = 0.004, OR = 2.225, 95% CI = 1.277–3.877). These findings highlight the importance of MASP2 genetic polymorphisms in the lectin pathway of complement activation and susceptibility to HTLV‐1 infection.